Mediasi Burnout Pada Pengaruh Ambiguitas Dan Konflik Terhadap Komitmen Pegawai Manufaktur Di Bantul - Choirunnisak, Choirunnisak; Kurniawan, Ignatius Soni (Jurnal Ekonika : Jurnal Ekonomi Universitas Kadiri, 2020)
This study aims to examine the effect of role ambiguity and role conflict on employee commitment with burnout as a mediating variable. The research sample was 120 employees of four manufacturing companies located in Bantul, Yogyakarta. Research findings suggest that burnout mediates the influence of ambiguity and role conflict on commitment. The study produced an interesting finding that role ambiguity had a negative effect on burnout and role conflict had a positive effect on commitment.